Enhancing pressure ulcer healing and tissue regeneration by using N-acetyl-cysteine loaded carboxymethyl cellulose/gelatin/sodium alginate hydrogel - Aldaghi, Niloofar; kamalabadi-Farahani, Mohammad; Alizadeh, Morteza; Alizadeh, Akram; Salehi, Majid (Biomedical engineering letters, 2024)
Prolonged pressure on the skin can result in pressure ulcers, which may lead to serious complications, such as infection and tissue damage. In this study, we evaluated the effect of a carboxymethyl cellulose/gelatin/sodium alginate (CMC/Gel/Alg) hydrogel containing N-acetyl-cysteine (NAC) on the healing of pressure ulcers. Pressure ulcers were induced by applying a magnet to the dorsum of rat skin. The wounds were then treated with sterile gauze, ChitoHeal Gel ® , and CMC/Gel/Alg hydrogel dressings with or without NAC for the other groups. We evaluated the morphology, weight loss, swelling, rheology, blood compatibility, cytocompatibility, antioxidant capacity, and wound scratch of the prepared hydrogel. MTT assay revealed that the optimum concentration of NAC was 5 mg/ml, which induced higher cell proliferation and viability. Results of the histopathological evaluation showed increased wound closure, and complete re-epithelialization in the hydrogel-containing NAC group compared to the other groups. The CMC/Gel/Alg/5 mg/ml NAC hydrogel dressing showed 84% wound closure at 14 days after treatment. Immunohistochemical results showed a decrease in the level of TNF-α on day 14 compared day 7. Results of the qPCR assay revealed that NAC hydrogel increased the expression of Collagen type I and TGF-β1 and decreased MMP2 and MMP9 mRNA on the 14th day. The results suggest that the CMC/Gel/Alg/5 mg/ml NAC hydrogel with antioxidant properties is an appropriate dressing for wound healing.